Electronic Retailing : The Impact Of Internet And Benefits Gained By Malaysia Hybrid Retailers From The Coordination Of Electronic And Physical Channels - Lan, Ng Lee (2003)
This research describes the rationale behind a study of hybrid retailers in Malaysia.These retailers employ both electronic and physical channels to support the downstream sales of goods and services to end users. In order to create synergies between physical and electronic channels, hybrid retailers will need to coordinate their channels. This research paper presents a survey questionnaire that is designed to test whether such channel coordinate is indeed beneficial for hybrid retailers. The research will describe the impact or challenges taht might be faced by Malaysia retailers who may choose Internet as a new form of doing business.